Food Composition of Frigate Tuna (Auxis thazard Lacepède,1800) Caught by Fisherman in West Sumatra Waters - Saniyyah, Jauharah; Nofrita, Nofrita; Nurdin, Jabang (Jurnal Biologi Tropis, 2025)
Frigate tuna (Auxis thazard) is a pelagic and neritic fish resource that has economic value. Fish diet is one of the important information in monitoring the sustainability of fisheries resources in the future. This study aims to determine the composition of food and determine the Index of Preponderance of frigate tuna caught by fishermen in West Sumatra waters. The method used in this study was random sampling by taking 98 samples of frigate tuna obtained from the catch of fishermen in West Sumatra waters landed at the Air Bangis Fish Landing Center, West Pasaman Regency, and Gaung Fish Auction Site, Padang. The analysis used the Index of Preponderance to determine the main food, additional food, and complementary food. The results showed the composition of food in the stomach of frigate tuna consisted of 3 groups of organisms, namely zooplankton (61.04%), phytoplankton (31.82%), and pisces (7.13%). The main food of frigate tuna is zooplankton (62.10%), while the additional food are phytoplankton (27.73%), and pisces (10.16%). The availability of frigate tuna food in West Sumatra waters supports the sustainability of the frigate tuna population in these waters.